2017
DOI: 10.1111/ases.12327
|View full text |Cite
|
Sign up to set email alerts
|

Serosal and muscular layers incision technique in laparoscopic surgery for gastric gastrointestinal stromal tumors

Abstract: Laparoscopic wedge resection with SAMIT is technically and oncologically safe. It is useful for treating gastric gastrointestinal stromal tumors, including those close to the esophagogastric junction or pyloric ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Fujishima et al reported a modified CLEAN-NET technique, modifying the resection and closure procedure using laparoscopic stapling devices from full-layer stapling to only mucosal layer and adding seromuscular closure by handsewn suturing. This technique enabled resect the gastric SMTs near the EGJ or the pyloric ring without any stenosis [21]. In our case, the tumor was over 3 cm and located at the posterior wall near the cardia of the stomach.…”
Section: Discussionmentioning
confidence: 74%
“…Fujishima et al reported a modified CLEAN-NET technique, modifying the resection and closure procedure using laparoscopic stapling devices from full-layer stapling to only mucosal layer and adding seromuscular closure by handsewn suturing. This technique enabled resect the gastric SMTs near the EGJ or the pyloric ring without any stenosis [21]. In our case, the tumor was over 3 cm and located at the posterior wall near the cardia of the stomach.…”
Section: Discussionmentioning
confidence: 74%
“…The mucosal tissue is pulled out toward the outside of the stomach and the stretched mucosa is cut together with a minimal area of the full layer of the stomach wall. The greatest feature of these procedures is their non‐exposure technique, which may eliminate the risk of tumor cell seeding in patients with GIST with ulceration …”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that this style of surgery did not increase the risk of dissemination even in GIST with ulceration . The CLEAN‐NET, Lift and Cut, or SAMIT (laparoscopic wedge resection with the serosal and muscular layers incision technique) approaches all use a seromuscular incision to preserve the continuity of the mucosa, which works as a stretched a barrier in “CLEAN‐NET” . The mucosal tissue is pulled out toward the outside of the stomach and the stretched mucosa is cut together with a minimal area of the full layer of the stomach wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic endoscopic cooperative surgery (LECS) and modified LECS procedures such as inverted LECS, non-exposed endoscopic wall-inversion surgery (NEWS), combination of laparoscopic and endoscopic approaches to neoplasia with non-exposure technique (CLEAN-NET), serosal and muscular layers incision technique (SAMIT) have been recently developed to achieve partial resection with minimal gastric deformity. 1,2 Each technique has advantages and disadvantages; the appropriate technique is selected based on tumor characteristics. Intragastric surgery is another effective procedure which helps prevent deformities, especially for submucosal intraluminal tumors located around the esophagogastric junction (EGJ).…”
Section: Introductionmentioning
confidence: 99%